Pemberdayaan UMKM Tradisional Budin Keripik melalui Digital Branding di Desa Tempel Jaya - Hayrasyirah Ryazinharwa; Sherly Putri Revika; Fadli Febriansyah Zen; Khalishah Khirman Fadhilah; Nabilah Ramadhani; Yusniah Yusniah (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial pillar of the Indonesian economy, yet they often face significant constraints in marketing and branding, especially in rural areas with limited access. Reliance on traditional word-of-mouth promotion leads to a narrow market reach and low product competitiveness. This community service activity aims to empower the "Budin Keripik" MSME in Tempel Jaya Village, a home-based business operating since 2020, through the implementation of a comprehensive digital branding strategy. The implementation method adopted three main stages: planning, which included field observations and in-depth interviews with the owner to identify key problems such as the lack of visual identity and digital promotion; implementation, which focused on practical interventions like creating banners, designing a logo and packaging labels, setting up social media accounts (Instagram), and registering the business location on Google Maps to increase visibility; and mentoring, which involved technical training on digital promotion, content management, and the use of relevant hashtags to reach a wider audience. The intervention results show a significant positive impact, not only in material aspects like improved product visual appeal and broader marketing reach but also in non-material aspects such as an increase in the business owner's self-confidence in promotion. This initial success proves that digital branding is an effective and applicable strategy for enhancing the competitiveness of traditional MSMEs. However, the sustainability of this program faces challenges like limited capital for production scaling and a need for continuous development of digital literacy, thus requiring further support for long-term local economic strengthening.